Effects of Weight-Bearing Biofeedback Training on Functional Movement Patterns Following Total Knee Arthroplasty: A Randomized Controlled Trial - Christiansen, Cory L. (J Orthop Sports Phys Ther, 2015)
STUDY DESIGN: Randomized controlled trial. OBJECTIVES: Examine the effects of weight-bearing (WB) biofeedback training on WB symmetry and functional joint moments following unilateral total knee arthroplasty (TKA). BACKGROUND: Individuals post unilateral TKA place more weight on the non-surgical limb compared to the surgical limb during function. It is unknown if targeted intervention can improve surgical limb use and resolve altered movement patterns. METHODS: Twenty-six patients were randomized to 2 groups: RELOAD or CONTROL. The RELOAD group had standard of care rehabilitation augmented with WB biofeedback training and the CONTROL group had dose-matched standard of care. Lower limb weight-bearing ratios (WBRs) were measured preoperatively and 6 and 26 weeks after TKA during a Five Times Sit-to-Stand Test (FTSST) and walking. Secondary outcomes were FTSST time, walking speed, and lower limb joint moments during the FTSST and walking. RESULTS: No between-group differences were found in WBR. FTSST time improved in the RELOAD group compared to the CONTROL group at 6 (P=.021) and 26 weeks (P=.021) and there was a tendency for improved walking speed in the RELOAD group at 26 weeks (P=.068). There were no between-group differences in knee extension moment during the FTSST. Surgical-limb knee extension moments during walking increased from baseline to 26 weeks in the RELOAD group and decreased in the CONTROL group (P=.008). CONCLUSION: WB biofeedback training had no effect on functional WB symmetry or knee extension moments during the FTSST. However, the biofeedback training resulted in increases of knee extension moments during gait and improved FTSST times. LEVEL OF EVIDENCE: Therapy, level 2b.